Comparative Analysis of the Effectiveness of Zakat and Government Programs in Reducing Poverty in Indonesia - Karimullah, Suud Sarim (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2025)
The issue of poverty in Indonesia is a multidimensional challenge that requires a comprehensive approach to address it. This research aims to answer this problem by comparing the effectiveness of zakat and government programs in Indonesia's context of poverty reduction. The method used in this research is a qualitative and quantitative approach with comparative analysis to compare the effectiveness of zakat and government programs involving data triangulation to reduce bias and increase confidence in the research results. The results show that zakat has great potential in alleviating poverty and supporting sustainable socio-economic development in Indonesia. Through efficient management and collaboration with government programs, zakat can improve people's welfare and reduce inequality. Integrating zakat and the state budget expands the intervention scope, including empowering low-income people through training, education, and business development. The synergy between zakat and government programs, strengthened by coordination and inclusive approach, can contribute significantly to creating a prosperous and poverty-free society. This is the concept of maqāṣid asy-syarīah, which aims to achieve the welfare of humanity in both worldly and ukhrawi aspects.